Insight into hydrogen bonding of terephthalamides with amino acids: Synthesis, structural and spectroscopic investigations. Issue 20 (18th May 2017) - Hachuła, Barbara; Polasz, Anna; Książek, Maria; Kusz, Joachim; Kozik, Violetta; Matussek, Marek; Pisarski, Wojciech
Abstract: Several bis -terephthalamides based on methyl esters of amino acids including glycine(1), β -alanine(2), γ -aminobutyric acid(3) and ε -aminocaproic acid(4), X(CH2 ) n HNOCC6 H4 CONH(CH2 ) n X (XCO2 CH3, n  = 1, 2, 3 and 5), have been synthesized and characterized by single-crystal X-ray diffraction and spectroscopic methods: FT-IR, polarized FT-IR, Raman, 1 H NMR and 13 C NMR. The four structures assemble via classical NH⋯O hydrogen bonds between amide functionalities linking the molecules into chains parallel to the short axis. The analysis of polarized IR spectra of pure and deuterated compounds reveals that a weak interchain (" through-space" ) exciton coupling involves two closely-spaced hydrogen bonds belonging to two different adjacent chains. The exciton coupling magnitude decreases with the addition of methylene groups to the terephthalamide system. Isotope effects in terephthalamides show that the distribution of protons and deuterons in the crystalline lattice depends on the strength of the exciton couplings involving hydrogen bonds. Graphical abstract: The relationship between the length of amino acid side chain in four terephthalamides and the exciton coupling magnitude is presented. Highlights: The crystal structures of new bis -terephthalamides were determinated. ATR-IR and Raman spectra of bis -terephthalamide crystals were recorded. Polarized IR spectra of hydrogen bonds in terephthalamide crystals were measured. The interchain vibrational exciton coupling mechanism was analyzed. Isotopic effects in the crystalline spectra were elucidated.